Warranted religion: answering objections to Alvin Plantinga's epistemology - CORRIGENDUM - McNabb, Tyler Dalton ca. 20./21. Jh. (Religious studies, 2015)
Warranted religion: answering objections to Alvin Plantinga's epistemology - CORRIGENDUM - Volume 51 Issue 4 - TYLER DALTON MCNABB